2023
DOI: 10.3390/jpm13030477
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Graft Healing in 2 Years after “Tension Suspension” Remnant-Preserving and Non-Remnant-Preserving Anatomical Reconstruction for Sherman Type II Anterior Cruciate Ligament Injury

Abstract: Purpose: To evaluate the degree of graft healing after “tension suspension” reconstruction of “Sherman II” anterior cruciate ligament injuries versus non-remnant preserving anatomical reconstruction and to compare the clinical outcomes of the two procedures. Method: The clinical data of 64 patients were retrospectively included. There were 31 cases in the “tension suspension” remnant-preserving reconstruction group and 33 cases in the non-remnant-preserving anatomical reconstruction group. The International Kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…More precisely, several surgical approaches for femoral tunnel positioning during remnant‐preserving ACLR have been proposed: some articles used intraoperative fluoroscopy [33]; some used the lateral intercondylar ridge (LIR) as a landmark [37]; and some used the remnant itself to locate the femoral tunnel [12]. Although all of the above methods could effectively create the femoral tunnel while preserving remnants [11], several studies still showed that the remnant could affect the accuracy of femoral tunnel positioning [1, 18].…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, several surgical approaches for femoral tunnel positioning during remnant‐preserving ACLR have been proposed: some articles used intraoperative fluoroscopy [33]; some used the lateral intercondylar ridge (LIR) as a landmark [37]; and some used the remnant itself to locate the femoral tunnel [12]. Although all of the above methods could effectively create the femoral tunnel while preserving remnants [11], several studies still showed that the remnant could affect the accuracy of femoral tunnel positioning [1, 18].…”
Section: Discussionmentioning
confidence: 99%